PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Antari, Ni Putu Gina Sukma; Sedana, Ida Bagus Panji (E-Jurnal Manajemen; Vol 7 No 2 (2018)DO - 10.24843/EJMUNUD.2018.v7.i02.p19, 2018)
ABSTRACT The financial performance of local government is reflection of successful the local government in managing the finance of region. This research aims to determine the significance of the effect locally generated revenue and capital expenditure on the financial performance of the local government. This research is conducted on the Regencies/Cities in Bali Province. The data used in this research is secondary data from the Government Finance Statistics report of Regencies/Cities in Bali Province year 2011-2015. The nonparticipant observation method is used for data collection and the analysis technique used is the multiple linear regression. The research result using the multiple linear regression analysis shows that the locally generated revenue has positive and significant effect towards the local government’s financial performance. Capital expenditure has negative and significant effect towards the local government’s financial performance. Keyword s : locally generated revenue , capital expenditure , financial performance of local government